2020
DOI: 10.1080/17425247.2020.1747430
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, open-label study to evaluate the safe and effective use of a new electromechanical auto-injection device for self-injection of certolizumab pegol

Abstract: Background: ava® is a new reusable electromechanical auto-injector (e-Device) with disposable, singleuse certolizumab pegol (CZP) dispensing cartridges. Methods: RA0098 (NCT03357471) was a US, multicenter, open-label, phase 3 study designed to assess whether the e-Device can be used safely and effectively by self-injecting patients. CZP pre-filled syringe (PFS) self-injecting patients (≥18 years) diagnosed with rheumatoid arthritis, axial spondyloarthritis, psoriatic arthritis, plaque psoriasis, and Crohn's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Tatla et al reported a similar study to evaluate the safe and effective use of electromechanical auto‐injection device for self‐injection of CZP in adult patients. After 4 weeks of CZP administration by the AVA®, 89.2% of the patients reported a preference for the e‐Device compared to the prefilled syringe as well as our results 8 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Tatla et al reported a similar study to evaluate the safe and effective use of electromechanical auto‐injection device for self‐injection of CZP in adult patients. After 4 weeks of CZP administration by the AVA®, 89.2% of the patients reported a preference for the e‐Device compared to the prefilled syringe as well as our results 8 …”
Section: Discussionsupporting
confidence: 84%
“…After 4 weeks of CZP administration by the AVA ® , 89.2% of the patients reported a preference for the e-Device compared to the prefilled syringe as well as our results. 8 The main technical problems with AVA ® device that have occurred during the study have been the clogging of the AVA ® devices with used cartridges after its injection. This is due to the management of patients during the withdrawal of used cartridges and AVA ® security system, so we conclude that it is very important to have spare AVA ® devices in the hospital pharmacy and/or other CZP devices to avoid delays in doses that can cause problems.…”
Section: Discussionmentioning
confidence: 99%
“…Mean age was 52 years (SD: 13 years) and approximately half of patients were in the Q2W schedule treatment group (53%; 37/70). At Visit 1, 68 (100%) patients completed both the pre- and post-injection ASI modules; at Visit 2, 68 (100%) patients completed the pre-injection module, of whom 65 (95.6%) completed the post-injection module; 3 patients did not complete the post-injection module [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pilot instrument was refined using the patient feedback and administered in RA0098 (NCT03357471), a multicenter, open-label, phase 3 clinical study conducted in the USA that assessed the ability of adult patients already self-injecting CZP using the PFS to safely and effectively self-inject CZP using ava ® [ 16 ]. Administering the instrument in RA0098 enabled qualitative review and evaluation of its psychometric properties.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, e-Device aims to minimize the patient needle phobia, and the concern about safety in the treatment administration, giving the patient an electronic device that provide the administration (57). Some patients reported a higher satisfaction, self-confidence, safety, and feasibility of e-Device, compared with pre-filled pen and syringes (55,58,59). The use of e-Device could both assess the adherence to treatment, enable patients to track their own data, perform self-assessments, and deliver questionnaires.…”
Section: Pso Patients At Higher Medium/long-term Risk Of Developing Psamentioning
confidence: 99%